Análise de lajes nervuradas bidirecionais através de modelos simplificados - Cunha, José Carlos Aparecido de Carvalho e (2012)
The present work aims to study the waffle slabs taking into account the simplifications in the analysis of their behavior. The simplifications used concern the analysis of waffle slab by the equivalent solid slab, the considerations on the flexibility of the support beams, and the treatment of continuity between adjacent panels of slabs. The research supports in the experimental analysis, in the results of studies published, in the standard codes for design of reinforced concrete to base the simplifications adopted. One waffle slab in actual size and its equivalent solid slab are tested. The test results for the waffle slab are compared with the processing of the slab through computer programs for structural design. The costs of slabs in two buildings are compared when it adopts the simplified analysis method or grillage model.